PENGARUH KUALITAS PELAYANAN, CITRA MEREK, DAN KEPERCAYAAN TERHADAP LOYALITAS NABASAH BANK SYARIAH INDONESIA KOTA BENGKULU PASCA INSIDEN GANGGUAN LAYANAN - Marsellina Fitri; Aan Shar; Selamet Fuadi (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2023)
The performance of sharia banking in Bengkulu Province increased in the fourth quarter of 2022. One of them is Bank Syariah Indonesia. However, recently there was an incident of service disruption/temporary error in the Bank Syariah Indonesia (BSI) banking system. The state-owned sharia bank resulting from the merger of three state-owned banks experienced a service disruption incident in May 2023. This research will evaluate the impact of this incident on customer loyalty by considering service quality, brand image and trust. As a result of this incident, of course there are causes and effects that occur, for example customer loyalty. Therefore, this research aims to determine the influence of service quality, brand image and trust on the loyalty of customers who experience post-incident service disruption/temporary errors. This research uses descriptive quantitative research. The population in this research is Bank Syariah Indonesia customers in Bengkulu City with a total sample of 150 customers taken using purposive sampling technique. The data source used is primary data obtained from questionnaire results, while secondary data is through websites and article publications and others. The research results show that the variables of service quality, brand image and trust have a positive and significant effect on customer loyalty. This means that this research can conclude that Bengkulu City Bank Syariah Indonesia (BSI) customers remain loyal after the temporary service disruption incident